Capitalism : the future of an illusion - Block, Fred L. (University of California Press, 2018)
"Since the 1980's, a particular definition of the United States and the global economy as being "capitalist" has become hegemonic. In this view, a capitalist economy is autonomous, coherent, and needs to be regulated by its own internal laws. This view is an illusion. The reality is that economies organized around the pursuit of private profit are contradictory, incoherent, and heavily intertwined with politics and governmental action. But the illusion remains hugely consequential because it has been embraced by political and economic elites who are convinced that they are powerless to change this system. The reality is that the continuing vitality of the U.S. and the world economy requires a new period of major reforms on the scale of the New Deal and the building of new global institutions after World War II"--Provided by publisher.